Current Developments in Monetary and Financial Law, Vol. 1. (International Monetary Fund, 1999)
The papers published in this volume are based on an IMF seminar held in 1988 covering a broad range of topics dealing with monetary and financial law. Topics presented at the seminar focused on the liberalization of capital movements, data dissemination, the IMF's goals in financial surveillance and architecture, and responses to the financial crises in Asia and Latin America. Recent issues in the financial sector were addressed including the supervision of banks and the major international effort- the Basle Core Principles of Banking Supervision. Updates on insolvency and liquidation of banks as well as lender-of-last-resort issues were presented along with how payment systems are adjusting to continuous financial modernization and the resulting legal issues. The activities of the European Economic and Monetary Union (EMU) were discussed from several viewpoints as was the issue of good governance. Information was also provided on the developments in the enforcement of bank claims and the law of security.